2012
DOI: 10.1037/a0025356
|View full text |Cite
|
Sign up to set email alerts
|

Basic numerical capacities and prevalence of developmental dyscalculia: The Havana Survey.

Abstract: The association of enumeration and number comparison capacities with arithmetical competence was examined in a large sample of children from 2nd to 9th grades. It was found that efficiency on numerical capacities predicted separately more than 25% of the variance in the individual differences on a timed arithmetical test, and this occurred for both younger and older learners. These capacities were also significant predictors of individual variations in an untimed curriculum-based math achievement test and on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 53 publications
8
115
1
3
Order By: Relevance
“…However, the author points out the fact that the study had been conducted with children who attended the public educational system. Another factor is related to diagnostic criteria for DD, which should be bet- 13 found 3.4% in Cuba. These studies draw attention to the fact that mathematics difficulty and the DD should be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…However, the author points out the fact that the study had been conducted with children who attended the public educational system. Another factor is related to diagnostic criteria for DD, which should be bet- 13 found 3.4% in Cuba. These studies draw attention to the fact that mathematics difficulty and the DD should be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of MD is between 3-6% among children (Reigosa-Crespo et al, 2012;R. Shalev, Manor, Amir, & Gross-Tsur, 1993;von Aster, Schweiter, & Weinhold Zulauf, 2007;von Aster & Shalev, 2007) while there is less evidence in regard to prevalence rates among adults.…”
Section: Journal Of Numerical Cognitionmentioning
confidence: 99%
“…One open question concerns the impact of basic number processing deficits on math achievement. Reigosa-Crespo et al (2011) suggested that basic number deficits in multifactorial MLD may be somewhat compensated. Unknown is whether the same occurs in Del22q11.2.…”
Section: Discussionmentioning
confidence: 99%
“…General cognitive factors such as deficits in visuospatial and phonological processing and working memory impairments, have been shown to influence mathematical performance (Geary, 2011;Wilson & Dehaene, 2007). Evidence is accumulating that a significant proportion (approximately 3%) of school-age children may present a relatively pure form of MLD that is associated with basic deficits in number processing (Reigosa-Crespo et al, 2011) such as number sense or acuity of the approximate number system (ANS).…”
Section: Introductionmentioning
confidence: 99%